Teaching generative construction scheduling: Proposed curriculum design and analysis of student learning for the Tri-Constraint Method. (January 2022) - Hall, Daniel M.; Čustović, Irfan; Sriram, Ravina; Chen, Qian
Abstract: Construction management courses are increasingly teaching digital technologies and automation. The default method to teach construction scheduling remains the critical path method, which suffers from lack of automation, lack of dynamic change processes, and wrong assumptions about resource and spatial availability. New methods to automate construction scheduling, sometimes referred to as generative construction scheduling, have been developed but are seldom taught in construction management courses. This paper describes the design of a new curriculum to teach one new approach to construction scheduling called the Tri-Constraint Method. The proposed five-lesson, flipped-classroom curriculum is designed to illustrate limitations of the critical path method, explain the theoretical and computational foundations of a generative scheduling algorithm, and provide practical experience through implementation with state-of-the-art software. To measure the impact of the curriculum on student learning, the paper conducts a descriptive statistical analysis, a paired t -test, and an examination of qualitative feedback. Students who entered the course with either low or high prior knowledge of construction scheduling showed significant improvement in their understanding of the key concepts and the algorithmic approach behind the generative construction scheduling. Overall, this paper demonstrates how curriculum design in engineering informatics can combine theoretical understanding and practical implementation to understand generative construction scheduling. The dissemination of this and similar teaching curricula can ensure that future engineering practitioners avoid "black box" implementations of automation software in their future careers.